The C-terminal Six Amino Acids of the FNT Channel FocA Are Required for Formate Translocation But Not Homopentamer Integrity - Hunger, Doreen; Röcker, Marie; Falke, Dörte; Lilie, Hauke; Sawers, R. Gary (Frontiers in Microbiology, 2017)
FocA is the archaetype of the pentameric formate-nitrite transporter (FNT) superfamily of channels, members of which translocate small organic and inorganic anions across the cytoplasmic membrane of microorganisms. The N- and C-termini of each protomer are cytoplasmically oriented. A Y-L-R motif is found immediately after transmembrane helix 6 at the C-terminus of FNT proteins related to FocA, or those with a role in formate translocation. Previous in vivo studies had revealed that formate translocation through FocA was controlled by interaction with the formate-producing glycyl-radical enzyme pyruvate formate-lyase (PflB) or its structural and functional homologue, TdcE. In this study we analysed the effect on in vivo formate export and import, as well as on the stability of the homopentamer in the membrane, of successively removing amino acid residues from the C-terminus of FocA. Removal of up to five amino acids was without consequence for either formate translocation or oligomer stability. Removal of a sixth residue (R280) prevented formate uptake by FocA in a strain lacking PflB and significantly reduced, but did not prevent, formate export. Sensitivity to the toxic formate analogue hypophosphite, which is also transported into the cell by FocA, was also relieved. Circular dichroism spectroscopy and blue-native PAGE analysis revealed, however, that this variant had near identical secondary and quaternary structural properties to those of native FocA. Interaction with the glycyl radical enzyme, TdcE, was also unaffected by removal of the C-terminal 6 amino acid residues, indicating that impaired interaction with TdcE was not the reason for impaired formate transloction. Removal of a further residue (L279) severely restricted formate export, the stability of the protein and its ability to form homopentamers. Together, these studies revealed that the Y278-L279-R280 motif at the C-terminus is essential for bidirectional formate translocation by FocA, but that L279 is both necessary and sufficient for homopentamer integrity.